Brain MRI disease burden and sex differences in cognitive performance of patients with multiple sclerosis - Motyl, Jiri; Friedova, Lucie; Ganapathy Subramanian, Ranjani; Vaneckova, Manuela; Fuchs, Tom A; Krasensky, Jan; Blahova Dusankova, Jana; Kubala Havrdova, Eva; Horakova, Dana; Uher, Tomas (Acta neurologica Belgica, 2024)
BACKGROUND: Although there is evidence that shows worse cognitive functioning in male patients with multiple sclerosis (MS), the role of brain pathology in this context is under-investigated. OBJECTIVE: To investigate sex differences in cognitive performance of MS patients, in the context of brain pathology and disease burden. METHODS: Brain MRI, neurological examination, neuropsychological assessment (Brief International Cognitive Assessment in MS-BICAMS, and Paced Auditory Verbal Learning Test-PASAT), and patient-reported outcome questionnaires were performed/administered in 1052 MS patients. RESULTS: Females had higher raw scores in the Symbol Digit Modalities Test (SDMT) (57.0 vs. 54.0; p < 0.001) and Categorical Verbal Learning Test (CVLT) (63.0 vs. 57.0; p < 0.001), but paradoxically, females evaluated their cognitive performance by MS Neuropsychological Questionnaire as being worse (16.6 vs 14.5, p = 0.004). Females had a trend for a weaker negative correlation between T2 lesion volume and SDMT ([Formula: see text] = - 0.37 in females vs. - 0.46 in men; interaction p = 0.038). On the other hand, women had a trend for a stronger correlation between Brain Parenchymal Fraction (BPF) and a visual memory test (Spearman's [Formula: see text] = 0.31 vs. 0.21; interaction p = 0.016). All these trends were not significant after correction for false discovery rate. CONCLUSIONS: Although, females consider their cognition as worse, males had at a group level slightly worse verbal memory and information processing speed. However, the sex differences in cognitive performance were smaller than the variability of scores within the same sex group. Brain MRI measures did not explain the sex differences in cognitive performance among MS patients.
Keywords: Magnetic Resonance Imaging; Female; Cognitive Dysfunction; Neuropsychological Tests; kognitivní poruchy; ženské pohlaví; Sex; Brain atrophy; neuropsychologické testy; lidé; Multiple Sclerosis; magnetická rezonanční tomografie; Lesion volume; roztroušená skleróza; mozek; Cognition Disorders; Sex Characteristics; kognice; Male; Brain; pohlavní dimorfismus; kognitivní dysfunkce; Cognition; MRI; mužské pohlaví; Multiple sclerosis; Humans